Pure Bromide‐Based Perovskite Nanoplatelets for Blue Light‐Emitting Diodes. Issue 10 (9th May 2019) - Peng, Shaomin; Wang, Sisi; Zhao, Dandan; Li, Xiaojun; Liang, Chao; Xia, Junmin; Zhang, Tianqi; Xing, Guichuan; Tang, Zikang
Abstract: Metal halide perovskites witness a huge development in light‐emitting diodes (LEDs) triggered by their unique optical and optoelectronic properties. However, blue emission perovskite LEDs lag behind their red and green counterparts in efficiency, due to the difficulties in synthesizing stable materials and maintaining quantum efficiency in thin films as high as in solution. The nanoplatelets (NPLs), with exciton binding energies up to several hundreds of meV, exhibit fundamentally different excitonic behavior from 0D nanocrystals. Meanwhile the bandgap tunability with thickness makes them promising for blue optoelectronic devices. Here, a brief review on recent progress in perovskite light emission, and the opportunities and challenges in pure bromide‐based perovskite NPLs for the blue‐emitting regime are provided. In particular, the important roles of surface ligands and emitting layer quality on devices are highlighted. The trade‐off between well surface passivation and efficient charge transportation is analyzed. Furthermore, it is recommended that more efforts should be put on exploring the carrier dynamics in NPLs, which act as guidelines for optimization of materials and improvement of devices. Abstract : The nanoplatelets (NPLs) are promising for blue optoelectronic devices due to their large exciton binding energy and thickness‐tunable bandgap. Here, recent advances and opportunities in pure bromide‐based perovskite NPLs for blue emission are provided. The important roles of surface ligands and emitting layer quality on devices are highlighted. The trade‐off between surface passivation and charge transport is analyzed.